Teaching English Vocabulary to Young Learners through Group Work - Dhian Marita Sari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
Over the last few decades, teaching English become a phenomenon in our country, especially for young learners. English is taught as a main subject in kindergarten and elementary schools. Like any other children, young learners accept new foreign languages easily, but they get bored very fast if the teacher is teaching them using the old conventional methods and techniques. This paper aims to prove that group work is an effective technique used for young learners' vocabulary acquisition. The study used a quantitative method, with a sample of fifth-grade students in SD Wojo Yogyakarta. The population consisted of 48 students, who were divided into a control class and an experimental class. The experimental class is a class that learns vocabulary through group work, while the control class is a class that conducts conventional methods. The collected data were analyzed using a T-test. The T-test score of 1.68 was found to be less than 0.05. This means that there are differences between learning in groups (group work) and traditional methods. Moreover, group work is more effective than traditional methods in improving young learners' vocabulary mastery.